The Effect Of Different Natural Feed on the Growth and Survival Rate of Pawas Larvae (Osteochilus hasselti C.V) - Elsi Kumala Sari; Sukendi '; Nuraini ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted in March to May 2016 in the Laboratory of Fish Hatchery and Breeding Faculty of Fisheries and Marine Sciences University of Riau. The purpose of this research was to know the effect of the several combination natural feed on the growth and survival rate of Osteochilus hasselti C.V larvae.This research used the experimental method, while the experimental design that was used completely randomized design (CRD) with six treatments and three replication : P1 is combination Artemia sp. 10 days + Kutu Air 10 days + Tubifex sp. 20 days, P2 is combination Artemia sp. 10 days + Kutu Air 20 days + Tubifex sp. 10 days, P3 is combination Artemia sp. 20 days + Kutu Air 10 days + Tubifex sp. 10 days, P4 is combination Kutu Air 10 days + Tubifex sp. 30 days, P5 is combination Kutu Air 20 days + Tubifex sp. 20 days, P6 is combination Kutu Air 30 days + Tubifex sp. 10 days.The result showed the best treatment was feeding with P4 combination Kutu Air 10 days + Tubifex sp. 30 days the growth of absolute weigh that produces 0,895 grams, the growth of absolute length is 3,870 cm, the daily growth rate of 12,982%, while the best survival rate found in the combination natural feeding P3 is combination Artemia sp. 20 days + Kutu Air 10 days + Tubifex sp. 10 days and P5 is combination Kutu Air 20 days + Tubifex sp. 20 days each 90%. The water quality parameters during research were temperature 26,2-28,3oC, pH 6,8-7,3, dissolved oxygen 2-6,4 mg/l.Key words: Combination, Natural food, Osteochilus hasselti C.V, growth, and survival